Gold nanoparticles supported on three‐dimensional nitrogen‐doped graphene: an efficient catalyst for selective aerobic oxidation of hydrocarbons under mild conditions. (4th May 2015) - Mahyari, Mojtaba; Laeini, Mohammad Sadegh; Shaabani, Ahmad; Kazerooni, Hanif
<x xml:space="preserve">Abstract</x> The development of efficient and selective aerobic oxidation of alkylarenes to form more functional compounds by heterogeneously catalysed routes still presents a great challenge in the fine chemical industry and is a major research topic. In this work, gold nanoparticles supported on three‐dimensional nitrogen‐doped graphene‐based frameworks (Au NPs@3D‐(N)GFs) were successfully synthesized and found to have an impressive performance as bifunctional catalysts (nitrogen dopant as base and gold nanoparticles as active site) in the controlled oxidation of alkylarenes. The catalyst was found to be a simple bench top, stable, recyclable and selective catalytic system for the aerobic oxidation of various types of alkylarenes into their corresponding ketones at room temperature under environmentally friendly conditions with good yields and high selectivity. Copyright © 2015 John Wiley & Sons, Ltd.